The value of dicalcium phosphate, Vitamin A and grinding corn for calves fed prairie hay - Smith, E.F.; Richardson, D.; Curtis, R.G.; Dunn, L. (Kansas Agricultural Experiment Station, 2011)
The 60 good-to-choice grade Hereford calves used in this test came from near Fort Davis, Texas. They were assigned 10 to a lot on the basis of weight. All lots received all the prairie hay they would consume, about four pounds of corn each daily, and 1.25 pounds of soybean meal; where Vitamin A (15,000 I.U. daily) and dicalcium phosphate (0.1 pound per head daily) were fed they were mixed with the soybean meal. In the lots fed ground corn it was ground medium coarse or between fine and coarse ground: the modulus of fineness was 4.34.
Keywords: Beef; Dicalcium phosphate; Vitamin A; Ground corn; Prairie hay